Effectiveness of a Barber-Based Intervention for Improving Hypertension Control in Black Men: The BARBER-1 Study: A Cluster Randomized Trial - Victor, Ronald G. (2010)
CONTEXT: Barbershop-based hypertension (HTN) outreach programs for black men are becoming increasingly common, but whether they are an effective approach for improving HTN control remains uncertain. OBJECTIVE: To evaluate whether a continuous high blood pressure (BP) monitoring and referral program conducted by barbers will motivate male patrons with elevated BP to pursue physician follow-up, leading to improved HTN control. DESIGN, SETTING, AND PARTICIPANTS: Cluster randomized trial (Barber-Assisted Reduction in Blood Pressure in Ethnic Residents [BARBER-1]) of HTN control among black male patrons of 17 black-owned barbershops in Dallas County, Texas (March 2006-December 2008). INTERVENTION: Black male patrons of participating barbershops underwent 10-week baseline BP screening. Study sites were then randomized to a comparison group (8 shops, 77 hypertensives/shop) that received standard BP pamphlets or an intervention group (9 shops, 75 hypertensives/shop) in which barbers continually offered BP checks with haircuts and promoted physician follow-up with gender-specific peer-based health messaging. After 10 months, follow-up data were obtained. PRIMARY OUTCOME MEASURE: Change in HTN control rate for each barbershop. RESULTS: The HTN control rate increased more in intervention-arm barbershops than in comparison-arm barbershops (absolute group difference, 8.8%; 95% confidence interval [CI], 0.8 to 16.9%; P=0.036); the intervention effect persisted after adjustment for covariates (P=0.031). A marginal intervention effect was found for systolic BP change (absolute group difference: −2.5 mmHg; 95% CI, −5.3 to 0.3 mmHg; P=0.08). CONCLUSION: The effect of BP screening on HTN control among black male barbershop patrons was improved when barbers were enabled to become health educators, monitor BP, and promote physician referral. Further research is warranted. Trial registration clinicalTrials.gov Identifier NCT00325533